Hubungan Manajemen Waktu dengan Prokrastinasi Siswa Kelas XII di SMA Negeri 6 Padang - Rahmatika Laila Adhani; Linda Fitria; Rini Sefriani (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
This research aims to determine the relationship between time management and procrastination in class XII students at SMA Negeri 6 Padang in the 2024/2025 academic year. The type of research used in this research is quantitative. The population in this study was 356 class XII students registered in the 2024/2025 academic year, with a sample of 188 students, using proportional random sampling. The instrument used in collecting data for this research was a questionnaire prepared according to the Likert scale model. Data analysis was carried out using statistical programs on SPSS 29 and Microsoft Excel computers. Based on data analysis, the hypothetical results obtained were that the rcount value was 0.589 while rtable was 1.43 because the rcount value was greater than rtable (0.589>1.43), so there was a significant positive relationship between time management and procrastination in class XII students at SMA Negeri 6 Padang. The more students are able to manage their time, the more students' academic procrastination can be reduced.